Hermeneutics as cross-cultural encounter: Obstacles to understanding - Rohrbaugh, Richard L. (HTS teologiese studies, 2006)
It is a curious fact that while most people intuitively understand the potential for misunderstanding in face-to-face cross-cultural conversations, no such difficulty is anticipated when reading cross-culturally. Thus Westerners automatically assume they can read the Bible without taking account of its origins in an ancient Mediterranean culture that was sharply different to anything in the modern West. This article will describe the problem and then explore six major obstacles to cross-cultural communication (written as well as oral) that play a role in Western attempts to read a Mediterranean Bible. While a number of other significant obstacles could be cited, those addressed will suffice to make the point that it is time for Western scholars to acknowledge that the peculiarities of our cognitive style, language and mode of communication create disconnects with biblical texts of which we have simply not been aware.